Hope and other superpowers : a life affirming, love-defending, butt-kicking, world-saving manifesto - Pavlovitz, John (Simon & Schuster, 2018)
It<U+2019>s exhausting to give a damn these days, isn<U+2019>t it? Perhaps you<U+2019>re feeling anguished about what you see on the news or in your social media timeline, or by your personal circumstances, and are paralyzed waiting for political or religious leaders, or celebrities, to rescue us from it all. But what if you didn<U+2019>t have to wait for someone else? What if you could be the hero? This book<U+2014>a spirited call to action<U+2014>shows you how. In these pages, John offers a path away from the vitriol and toward com<U+00AD>passion, and a plan to transform our burdens into dreams and our outrage into activism. Drawing from lessons of beloved fictional superheroes, John shows us how to identify our origin story, build protective suits of armor, guard against our personal kryptonite, and vanquish our villains. He also identifies ten specific “superpowers” that we can enlist to make our lives and our world better. Along the way, he shares inspiring anecdotes and profiles about ordinary people who saw a gap in the world in empathy or kindness or gratitude and decided to fill it.